2005
DOI: 10.1115/1.2218343
|View full text |Cite
|
Sign up to set email alerts
|

Clamp Load Loss due to Elastic Interaction and Gasket Creep Relaxation in Bolted Joints

Abstract: An experimental study is presented in order to determine the clamp load loss due to elastic interaction and gasket creep relaxation in bolted joints. Studied parameters include the gasket material and thickness, bolt spacing, tightening sequence, fastener grip length, and level of the fastener preload. The joint is composed of two steel flanges and a gasket made of styrene butadiene rubber or flexible graphite. The flanges are fastened together using M12x1.75 Class 10.9 fasteners. Force washers are used to mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…A detailed survey of problems of estimating the performance of structural members by analyzing stress relaxation can be found in [2]. An example of influence of relaxation processes in elastomers on pipeline component performance is given in [3], where the influence of properties of sealing gaskets made of various materials on the tightening force of flange connection bolts is studied experimentally. It is shown that in connections with styrene-butadiene rubber gaskets the tightening force for the considered connection can decrease by 50% and more in five minutes.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed survey of problems of estimating the performance of structural members by analyzing stress relaxation can be found in [2]. An example of influence of relaxation processes in elastomers on pipeline component performance is given in [3], where the influence of properties of sealing gaskets made of various materials on the tightening force of flange connection bolts is studied experimentally. It is shown that in connections with styrene-butadiene rubber gaskets the tightening force for the considered connection can decrease by 50% and more in five minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric gaskets, however, demonstrate viscoelastic behavior and thus are limited in life due to creep relaxation. Nassar and Alkelani [5] created an experiment to measure the relationship between the thickness of the gasket and gasket deflection. Even though gasket relaxation is affected by gasket thickness, t G , a thicker gasket does not necessarily translate to increased relaxation.…”
Section: Mechanics Of Flanges and Re-torquementioning
confidence: 99%
“…Care was taken in the current study to ensure that the assembly and tightening procedures were not only consistent from experiment to experiment, but also done in accordance with standard practices associated with gasketed flange assemblies. Several tightening strategies have been studied by Nassar and Alkelani [5] (i.e., star, clockwise, and simultaneous). For the current study, bolts were initially hand-tightened.…”
Section: Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the preferred orientation and the cellular structure, the sheet is resilient in the direction perpendicular to the sheet. This resiliency contributes to the ability of flexible graphite to serve as a gasket, such as a gasket for sealing fluids [8,10]. Because graphite is chemically and thermally resistant, the gasket is particularly valuable for functioning under harsh environments.…”
Section: Introductionmentioning
confidence: 99%